In Defence of Extinctionism - Albersmeier, Frauke (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2014)
In Zoopolis, Donaldson and Kymlicka dismiss the abolitionist, or extinctionist approach in animal rights theory as insufficient in its theoretical foundation and disproportional regarding the means it promotes to prevent domesticated animals from suffering abuse by humans. Among the consequences of their counterproposal—granting domesticated animals citizenship—is an increased pressure to justify any interference with domesticated animals’ reproductive activities. This paper attempts to give such justification with reference to domesticated animals’ specific state of vulnerability, but also takes into account the interest of the mixed society to prevent overly demanding obligations. Even while recognizing existing domesticated animals as citizens, humans might be unable to fully meet their obligation to protect the most dependent of them, and therefore might be justified in conditionally subscribing to “extinctionism” and limiting these animals’ reproduction to the point of their ultimate extinction. Therefore, rather than upholding a strict opposition between extinctionism in any form and a political framework for animal rights, out of reasonable concern for the well-being of domesticated animals in the societies they have been placed in, a qualified extinctionist approach should be incorporated into the political framework developed in Zoopolis.